USE OF FOOTWEAR IN THE EVENT OF FOOT DEFORMITY IN TYPE 2 DIABETES MELLITUS PATIENTS - Dita Amita; Desi Susanti; Peri Zuliani; Nunu Harison; Yatimah Yatimah (Poltekkes Kemenkes Bengkulu, 2022)
One of the common complications of diabetes is diabetic foot problems such as deformities. Foot deformity is a risk factor for foot ulcers in diabetic patients. Diabetic foot complications such as diabetic ulcers and amputations will harm the quality of life of diabetic patients. This study aims to explain the relationship between wearing footwear and the incidence of foot deformity in people with type 2 diabetes. The research method was a quantitative study with a cross-sectional study design. The sample in this study consisted of 55 people with an accidental sampling technique. Data were collected through interviews and observations at the feet of the respondents. The types of foot deformities found in the respondents were hallux valgus 7.3%, hallux limitus 3.6%, hallux rigidus 3.6%, flat foot 5.5%, verruca plantaris 1.8%, and callus 7.3%. The results of this study were there is a relationship between the use of footwear and the incidence of foot deformity as evidenced by the Chi-Square statistical test results with a P value of 0.000 (P value < alpha). The results of the study found that the use of poor footwear can affect the shape of the feet, especially in patients with diabetes mellitus.